Fine Tuning of the HOMO–LUMO Gap of 6‐(Thiophen‐2‐yl) indolizino[3, 2‐c]quinolines and their Self‐Assembly to Form Fluorescent Organic Nanoparticles: Rational Design and Theoretical Calculations. Issue 1 (10th August 2020) - Park, Jaehyun; Lee, Ji Hye; Lim, Bumhee; Lee, Na Keum; Sim, Gyuseok; Ryu, Seol; Kim, Ikyon; Hwang, Hyonseok; Lee, Jeeyeon
Abstract: In this study, we designed and synthesized novel 6‐(thiophen‐2‐yl) indolizino[3, 2‐ c ]quinolines (IQs) guided by density functional theory (DFT) calculations and explored the optical properties of the IQ derivatives together with fractional atomic orbital contribution (FAOC) analysis. In accordance with the DFT predictions, the designed compound, IQ‐C9, with a methoxycarbonyl (MC) group attached to the C9 position of the IQ scaffold, displayed improved fluorescence quantum yields (QY) in solution and in the solid state along with bathochromic shifts compared to previous analogues. TEM images demonstrated that IQ‐C9 forms well‐defined nanoparticle structures (dimensions: 20×50 nm, aspect ratio: 2.3) in aqueous solution. Confocal images of IQ‐C9 ‐treated MCF7 cells revealed colocalization of IQ‐C9 with lipid droplets, highly dynamic subunits within cells involved in various metabolic disorders and cancers. Our results demonstrated that the analyses based on the FAOC coefficients and molecular orbital (MO) energy levels can be used as a computational method to predict spectral shifts for fluorophores and to design novel fluorescent probes for tracking dynamic cellular processes. Abstract : Mind the gap : Density functional theory (DFT) predictions of spectral shifts were employed to design a novel 6‐(thiophen‐2‐yl) indolizino[3, 2‐ c ]quinoline, IQ‐C9, with the ability to self‐assemble to form fluorescent organic nanoparticles (FONs). IQ‐C9 displayed improved quantum yields (QY) in solution and in the solid state along with bathochromic shifts compared to previous analogues.